Identification and characterization of two functional variants in the human longevity gene FOXO3 - Friederike Flachsbart (Nature Portfolio, 2017)
FOXO3 is one of the few established longevity genes. Here, the authors fine-map the FOXO3-longevity association to two intronic SNPs and, using luciferase assays and EMSAs, show that these SNPs affect binding of transcription factors CTCF and SRF and associate with FOXO3 expression.